Epistaxis-related hemolacria in a 6-year-old female after midfacial trauma: Epistaxis-related hemolacria - Demirer Çelik, Merve; Aslan, Deniz (Indian Journal of Case Reports, 2024)
Hemolacria (HL) is a rare condition characterized by the presence of blood in the tears. Bleeding associated with tears can occur in the context of infection, inflammation, trauma to the eye or surrounding structures, vascular tumors of the eye or surrounding structures, or retrograde epistaxis. We herein present a pediatric case with HL in the setting of epistaxis due to post-traumatic vessel injury without fracture, along with a literature review. Bleeding from the inferior lacrimal punctum was controlled by successful cauterization of damaged vessels and follow-up has remained uneventful for over a year. Bleeding from the eye is an alarming symptom, especially if it developed after facial trauma. However, physicians should be more aware that, in the absence of a fracture, HL due to retrograde epistaxis resulting from facial trauma can be a self-limited condition that is easily treated by controlling nasal hemorrhage.